The Effect of Player Transfers on Football Companies Valuation - Bács, Bence András (International Journal of Engineering and Management Sciences, 2022)
Transfer seasons are one of the most highlighted periods in world of football. The market of player rights forces the greatest european clubs with their enormous budgets to compete with each other in order to aquire the most talented and most succesful players. It is not uncommon to sign players for tens of millions of euros, to this extent these expenditures are seriously affecting clubs bottom line. However, despite the expenditure nature of player transfers the value of these clubs increase, based on the best known measurer for companies valuation: the stock exchange. In my research the effect of player transfers ont he valuation of football corporations are presented through market value development of stock market listed clubs namely Juventus and BVB Dortmund. Based on my results if the examined clubs were signing players according to a player transfer policy considered as succesful the value of examined clubs had increased through stock market price independently of player transfer balance. Moreover the effect of coronavirus could had been noticed, since both clubs valuation decreased heavily in the 2020 summer transfer window probably due to the revenue loss caused by the pandemic.